The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1111/jvim.17080
|View full text |Cite
|
Sign up to set email alerts
|

Safety and biologic activity of a canine anti‐CD20 monoclonal antibody in dogs with diffuse large B‐cell lymphoma

Gretchen P. McLinden,
Anne C. Avery,
Heather L. Gardner
et al.

Abstract: BackgroundTo explore the safety and utility of combining low dose single‐agent doxorubicin with a canine specific anti‐CD20 monoclonal antibody (1E4‐cIgGB) in client owned dogs with untreated B‐cell lymphoma.AnimalsForty‐two client‐owned dogs with untreated B‐cell lymphoma.MethodsA prospective, single arm, open label clinical trial of dogs with B‐cell lymphoma were enrolled to receive 1E4‐cIgGB and doxorubicin in addition to 1 of 3 immunomodulatory regimens. B‐cell depletion was monitored by flow cytometry per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(129 reference statements)
0
0
0
Order By: Relevance
“…Cancer immunology explores the mechanisms by which the immune system can detect and destroy cancer cells, as well as how tumors evade immune surveillance ( 3 ). Research in veterinary cancer immunology has revealed that, similar to humans, animals' immune systems can recognize cancer-specific antigens and mount a response ( 1 , 4 ). However, tumors often develop strategies to suppress the immune response, such as producing immunosuppressive cytokines or recruiting regulatory T cells that inhibit anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer immunology explores the mechanisms by which the immune system can detect and destroy cancer cells, as well as how tumors evade immune surveillance ( 3 ). Research in veterinary cancer immunology has revealed that, similar to humans, animals' immune systems can recognize cancer-specific antigens and mount a response ( 1 , 4 ). However, tumors often develop strategies to suppress the immune response, such as producing immunosuppressive cytokines or recruiting regulatory T cells that inhibit anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in veterinary cancer immunology include the development of novel immunotherapeutic approaches. These include cancer vaccines that stimulate the immune system to recognize and attack tumor cells, monoclonal antibodies that target specific cancer antigens, and checkpoint inhibitors that block proteins used by cancer cells to evade immune detection ( 4 , 6 , 7 ). Clinical trials in veterinary medicine have shown promising results, particularly in treating canine cancers like lymphoma ( 4 ) and osteosarcoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation